The Incidence rate of Asymptomatic Bacteriuria among LIMU students - Alariyibi, Ritaj (faculty of applied basic medical science - Libyan international medical university, 2022)
Escherichia coli is the most common organism associated with asymptomatic bacteriuria (ABU). In contrast to uropathogenic E. coli , which causes symptomatic urinary tract infections (UTI), asymptomatic bacteriuria is significant bacterial count in the urine, without symptoms of urinary tract infections (UTI) Urinalysis measurements were collected from 12 (50%) men and 12 (50%)women. The cutler media shows bacteria growth in female volunteers , but statistically There were statistically significant different in asymptomatic bacteriuria with gender (X2 , P=0.004) .
Keywords: Bacteriuria